Topology-Dependent Antifreeze Properties of Biomimetic Linear and Star-Shaped Peptoids - Lei Feng; Liugen Xu; Junhao Wen; Minghai Zhao; Amjad Ali; Naushad Ahmad; Jianwei Lu; Li Guo (Biomimetics, 2025)
Developing safe and efficient cryoprotectants is critical for effective cryopreservation in biomedical applications. Inspired by natural antifreeze proteins (AFPs), a series of linear and star-shaped peptoids featuring isopropanol side chains to mimic the amphiphilic characteristics of threonine were prepared. The effects of chain length and molecular topology on antifreeze properties were systematically investigated. Both ice recrystallization inhibition (IRI) and ice crystal growth suppression improved with increasing chain length, and star-shaped peptoids exhibited superior performance. Notably, the star-shaped peptoid S-(A6)3 demonstrated excellent antifreeze activity and low cytotoxicity, highlighting its promise as a novel, non-toxic alternative to conventional cryoprotectants like DMSO. These findings provide valuable insight into the structure-property relationship of peptoids for cryopreservation applications.